“Ocala” - A New Diploid Annual Ryegrass for the Southern U.S. - Ann R. Blount; Gordon M. Prine; Kevin E. Kenworthy; Paul Mislevy; Jeffery C. Jones; Paul E. Reith (EDIS, 2011)
Ocala, a new UF annual ryegrass, has excellent disease resistance and sufficient cold tolerance to be grown successfully in the southern annual ryegrass region of the U.S. It is a well-adapted, diploid annual ryegrass population. Parentage includes several advanced experimental annual ryegrass populations for Florida and Nebraska. This 1-page fact sheet was written by A.R. Blount, G.M. Prine, K.E. Kenworthy, P. Mislevy, J.C. Jones, and P.E. Reith, and published by the UF Department of Agronomy, October 2011.